2021
DOI: 10.1021/acs.biochem.1c00292
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Inhibition of the Reproduction of SARS-CoV-2 and Ebola Viruses by Remdesivir

Abstract: Remdesivir is an antiviral drug initially designed against the Ebola virus. The results obtained with it both in biochemical studies in vitro and in cell line assays in vivo were very promising, but it proved to be ineffective in clinical trials. Remdesivir exhibited far better efficacy when repurposed against SARS-CoV-2. The chemistry that accounts for this difference is the subject of this study. Here, we examine the hypothesis that remdesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Efficient selective incorporation of RDV-TP, calculated as ratio of efficiency of incorporation of ATP over RDV-TP, is seen with SARS-CoV-2 (0.3), HCV (0.9), EBOV (4.0), NiV (1.6) and RSV enzymes (2.7). In contrast, much higher selectivity values for LASV ( 20 ), CCHFV ( 41 ), and FluB (68) enzymes suggest poor RDV-TP substrate usage. The ability of a nucleotide analogue inhibitor to be incorporated by viral RdRp enzymes is largely dependent on variations in the residues that define the nucleotide binding site ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient selective incorporation of RDV-TP, calculated as ratio of efficiency of incorporation of ATP over RDV-TP, is seen with SARS-CoV-2 (0.3), HCV (0.9), EBOV (4.0), NiV (1.6) and RSV enzymes (2.7). In contrast, much higher selectivity values for LASV ( 20 ), CCHFV ( 41 ), and FluB (68) enzymes suggest poor RDV-TP substrate usage. The ability of a nucleotide analogue inhibitor to be incorporated by viral RdRp enzymes is largely dependent on variations in the residues that define the nucleotide binding site ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…For SARS-CoV-2 RdRp, it has been demonstrated that higher NTP concentrations can overcome inhibition at "i+3" ( 26 , 27 , 36 , 37 , 38 , 39 ). Others have therefore used a different terminology and refer to "delayed translocation" ( 39 ), “delayed chain extension” ( 39 ), “delayed stalling" ( 36 ), “delayed intervention" ( 40 ), or enzyme "pausing" ( 27 , 37 , 40 , 41 ). “Pausing” has also been observed on long templates that better mimic the RNA genome ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…RdRp shares significant homology within the RNA virus Coronaviridae family and is a popular target for SARS-CoV-2 repositioning studies due to a given drug’s prospect of high selectivity and low probability of associated cytotoxicity. , Many nucleoside analogues have been proposed due to low RdRp replication fidelity . Due to the inhibitory potential of remdesivir for the RdRp in Ebola virus, , several virtual screening campaigns were conducted. , Despite the lack of consensus for hits identified among the virtual repurposing campaigns, two of the in silico shortlisted drugs were reported among the hits identified in cell-based repurposing studies, namely, digoxin (a cardiac glycoside; EC 50 = 0.07 μM) and ritonavir (an HIV protease inhibitor; AC 50 = 22.53 μM). ,,, …”
Section: Target-based Sars-cov-2 Repositioning Screeningsmentioning
confidence: 99%
“…82,83 Many nucleoside analogues have been proposed due to low RdRp replication fidelity. 85 Due to the inhibitory potential of remdesivir for the RdRp in Ebola virus, 67,86 several virtual screening campaigns were conducted. [83][84][85]87 Despite the lack of consensus for hits identified among the virtual repurposing campaigns, two of the in silico shortlisted drugs were reported among the hits identified in cell-based repurposing studies, namely, digoxin (a cardiac glycoside; EC 50 = 0.07 μM) 20 and ritonavir (an HIV protease inhibitor; AC 50 = 22.53 μM).…”
Section: ■ Cell-based High-throughput Screensmentioning
confidence: 99%
“…Nevertheless, RMP-containing viral RNAs are likely nonfunctional and thus are partially responsible for the suppression of viral reproduction. 13 In fact, the incorporation of RDV and its effects on viral RNA production in the SARS-CoV-2 infected cell lines is highly strand dependent. 12 Therefore, a new class of anti-SARS-CoV-2 inhibitors could be rationally designed, including the formation of dead-end inhibitory ternary complexes at the pol active site, translocation-inhibited complexes, or exoribonuclease-inhibited complexes.…”
Section: Introductionmentioning
confidence: 99%